Biomonitoring of Effects and Accumulations of Heavy Metals Insults Using Some Helminth Parasites of Fish as Bio-Indicators in an Afrotropical Stream - Keke, Unique N.; Mgbemena, Amaka S.; Arimoro, Francis O.; Omalu, Innocent C. J. (Frontiers in Environmental Science, 2020)
Studies on biomonitoring the aquatic environment using host-parasite dynamics as bio-indicators of effects and accumulators of heavy metals insults are still scarce, particularly in the tropics. In our study, we aimed at elucidating the possible use of helminth parasites of fish in monitoring and controlling heavy metal pollution. Samples were collected from an anthropogenically polluted river in north central region of Nigeria over a period of 24 months (September 2014 and October 2016). Water, fish muscle, and fish parasites samples of three dominant fish species were collected, processed, and analyzed for copper, lead, manganese, iron, zinc, and chromium. The metal concentrations in parasites of: Clarias garienpinus was in the order of Fe > Zn > Cr > Mn > Pb > Cu; Tilapia zillii was in the order of Fe > Zn > Mn > Cu > Cr > Pb; and that of Raimas nigeriensis was in the order of Fe > Zn > Cr > Mn > Cu > Pb. The CCA ordination revealed strong relationships between fish parasites and heavy metals pollution. Generally, Fe, Zn, Mn, Cu, Cr, and Pb concentrations in the parasites of all fish species were clearly higher than those in the muscles of the fish hosts. Pb was not detected in the fish muscles of Raimas nigeriensis but was detected in the parasites of the fish, thus indicating high bioaccumulation capacity of the parasites. The close linkage between Eustrongylides sp. and zinc could mean that Eustrongylides sp. was an ideal surrogate for zinc pollution. This study revealed that intestinal helminthic parasites can be ideal surrogates for both effects and accumulation bioindication of heavy metal pollution.